A Brain for Life: How to Optimise Your Brain Health by Making Simple Lifestyle Changes Now - Gates, Nicola ([S.l.] : ABC Books, 2016)
Reduce your risk of dementia! Dementia is the second highest killer of Australians today - don't become a statistic! How we live has a powerful effect on our brain. So by making simple lifestyle changes, we can keep our brains strong as we age and reduce our risk of dementia. This practical, step-by-step guide will help you to build brain power and prevent brain burnout. Neuropsychologist Nicola Gates draws on cutting-edge research to explain the amazing roles our health and fitness, as well as mental activity, play in brain health. And she shares the simple steps we can all take to keep our brains fit and active. Discover: , ∗Why being mindful is essential for brain health , ∗Why a healthy gut means a healthy brain , ∗The heart-brain connection , ∗The critical link between exercise and brain fitness , ∗Why your brain wants you to stay social Don't wait for a crisis: Dr Gates can help you start making changes today for the best possible brain health - for life!.
Imprint: ABC Books.
Keywords: Brain -- Degeneration -- Prevention; Dementia -- Diet therapy; Dementia -- Prevention; Health behavior; Mental health; Health & Fitness - General; HEALTH & FITNESS|; Public health & preventive medicine; Australian; Health & Fitness